Features of structural and technological solutions for receiving system of small radio telescopes - E. N. Gluschechenko; A. M. Pylypenko; E. V. Slonin; I. K. Sunduchkov; V. V. Chmil (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The article presents new technological solutions and structural approaches for design of radiometric receiving systems for small diameter antennas. Problems which need to be dealt with in the process of realization of such systems are formulated. All the considered problems, both structural and technological, encountered when creating radiometric receiving systems for small diameter antennas, were not only tested on the mockups, but also successfully implemented in three sets of radiometric systems of modern radio astronomy facilities. In addition, the described approach to solving these problems is recommended for the wide application by the international VLBI service.